Using the generalized collage theorem for estimating unknown parameters in perturbed mixed variational equations - Garralda-Guillem, A.I.; Kunze, H.; La Torre, D.; Ruiz Galán, M. (Communications in nonlinear science & numerical simulation, 2020)
•Perturbed mixed variational problems: existence results.•A Galerkin scheme for solving perturbed mixed variational equations.•Stating a collage-theorem-type result for a perturbed variational problem and a related numerical algorithm. In this paper, we study a mixed variational problem subject to perturbations, where the noise term is modelled by means of a bilinear form that has to be understood to be “small” in some sense. Indeed, we consider a family of such problems and provide a result that guarantees existence and uniqueness of the solution. Moreover, a stability condition for the solutions yields a Generalized Collage Theorem, which extends previous results by the same authors. We introduce the corresponding Galerkin method and study its convergence. We also analyze the associated inverse problem and we show how to solve it by means of the mentioned Generalized Collage Theorem and the use of adequate Schauder bases. Numerical examples show how the method works in a practical context.